(untitled) (Mustansiria Dental Journal, 2018)
Gender stereotypes can lead to a variety of generalizations that affect the perceptions of patients. Pain mechanism start with peripheral stimuli which will initiate the afferent nerves fibers that will transmit the signals towards the central nervous system through the spinal cord into the cerebral cortex where the pain signal will be translated. The aim of this research is to evaluate the complex assessing of patient’s pain perception in relation to the gender of the dentist during normal teeth extraction. Samples in this study was composed of (50) patients, divided into two equal groups, first group treated by male students and the second’s group treated by female students. The results of statistical analysis of data showed that pain perception by the patients was in mild status more in male group 18(72%) than female group 4(16%),While in moderate was less in male group 5(20%) than female group 15(60%),and in sever also less in male group 2(8%) than female group 6 (24%). A significant difference was shown between the two students’ gender in case of moderate and sever pain status (Chi-square in moderate status 8.33 & p-value= 0.004 while in sever status 2.381 & 0.048respectively), while high significant difference in mild status (Chi-square15.91and P<0.01). In Conclusions: A statistical analysis showing that pain perception experienced by the patients treated by male students’ operator liable to be less than those treated by female students’ operator.